The Effect of local Pomegranate Peel powder of Some Pathogenic Bacteria and Food Spoilage Bacteria in Chilled Beef Burgers - Alzwei الطاهر عمر; Hussien لبنى علي (Journal of Pure & Applied Sciences, 2022)
This study aimed to identify the effect of adding different concentrations (0,3,6,9%) of the local pomegranate peel powder (al-shaftari), on the growth of some types of pathogenic and spoilage bacteria (aerobic bacteria, psychrotrophic bacteria and coliform bacteria), in ground beef patties “burger” that were stored for nine days at a temperature of 4-7°c. the results showed a gradual decrease in all tested bacterial groups of pomegranate peel powder added to ground meat tablets, where the highest inhibitory effect was at 9% concentration during cold storage periods (0,3, 6 and 9 days), where the averages of the total number of aerobic bacteria in the control sample 2.2 × 104 cfu/g, while in the tablets that contained 9% concentration of pomegranate peel powder, 2.1 × 104 cfu/g during storage time zero. while an increase in the numbers of aerobic bacteria was observed on the ninth day of cold storage, as it was 4.0×106 cfu/g at 3% concentration of pomegranate peel powder, while it decreased to 1.8×106 cfu/g at the concentration of 9% of the pomegranate peel powder. The results also showed decrease in the number of psychrotrophic bacteria at concentrations 3, 6 and 9% compared to the control sample, and the highest inhibitory effect was at the 9% concentration with an average of 1.4 x 106 cfu/g compared to the control sample was 3.4 x 106 cfu/g. the results also showed a decrease in the average numbers of coliform bacteria during the different periods of cold storage, as the number of coliform bacteria on the ninth day of the cold storage period for the control sample was 6.3 x 102 cfu/g and for the concentration of 9% of pomegranate peel powder was 4.1 x 102 cfu/g. it was found through the statistical analysis of the obtained results that the addition of pomegranate peel powder had a significant effect at the probability level (p ≥ 0.05) on the growth of all types of tested bacteria.